2013
DOI: 10.3109/02713683.2012.757326
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Amniotic Membrane as a Depot Carrier for Bevacizumab – AnIn-VitroModel for a Slow Release Mechanism

Abstract: In this in-vitro setting, we could demonstrate effective VEGF-blockade for up to 1 week by incubating HAM with bevacizumab. HAMs might be potentially used as a carrier for drugs delivered to the cornea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…For example, once an appropriate number of tubes have been formed, bevacizumab or other angiogenesis inhibitors can be added to retard the vascularization process before implantation. [49][50][51] As many cell types beyond endothelial cells are involved in vascularization in vivo, it remains to be seen whether these prevascular constructs would remain stable after implantation without accompanying perivascular cells. 52,53 If these additional cells are needed in vitro to ensure success in vivo, the optimum pore size is likely to be slightly larger than the values we report here, as additional space would be needed to facilitate supporting fibroblasts and pericytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, once an appropriate number of tubes have been formed, bevacizumab or other angiogenesis inhibitors can be added to retard the vascularization process before implantation. [49][50][51] As many cell types beyond endothelial cells are involved in vascularization in vivo, it remains to be seen whether these prevascular constructs would remain stable after implantation without accompanying perivascular cells. 52,53 If these additional cells are needed in vitro to ensure success in vivo, the optimum pore size is likely to be slightly larger than the values we report here, as additional space would be needed to facilitate supporting fibroblasts and pericytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tube formation can be maximized and overgrowth minimized by tuning the initial cell density and culture time. For example, once an appropriate number of tubes have been formed, bevacizumab or other angiogenesis inhibitors can be added to retard the vascularization process before implantation . As many cell types beyond endothelial cells are involved in vascularization in vivo , it remains to be seen whether these prevascular constructs would remain stable after implantation without accompanying perivascular cells .…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery systems have become a hot research topic in order to determine how to prolong the time a drug resides on the eye surface and to improve the bioavailability of drugs [27][28][29]. At present, ophthalmic surface drug delivery systems have been mainly focused on drug-loaded amniotic membranes [30][31][32] and drugloaded corneal contact lens [33][34][35]. Poor transparency and easy dissolution of amniotic membranes means they have limited clinical applications [31].…”
Section: Introductionmentioning
confidence: 99%
“…At present, ophthalmic surface drug delivery systems have been mainly focused on drug-loaded amniotic membranes [30][31][32] and drugloaded corneal contact lens [33][34][35]. Poor transparency and easy dissolution of amniotic membranes means they have limited clinical applications [31]. In addition, studies have shown that drug-loaded corneal contact lenses easily release a large amount of a drug in a short space of time, but they are less likely to meet the requirements of long-term drug release [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Yapılan son çalışmalarda, cerrahi öncesi bir süre antibiyotikli sıvıda bekletilen AZ'ın, transplantasyon sonrası yavaş salınımlı ilaç taşıyıcısı gibi davrandığını göstermiş ve AZ için yeni bir potansiyel kullanım alanı tanımlanmıştır. 7 Bu çalışmanın amacı, çeşitli oküler yüzey hastalıklarında kliniğimizde uyguladığımız AZ transplantasyon tekniklerinin sonuçlarını değerlendir mektir.…”
unclassified